Odpowiedź :
a) [tex](x-13)-(x-5)+2x=0\\x-13-x+5+2x=0\\2x-8=0\\2x=8\,|\div2\\\boxed{x=4}[/tex]
c) [tex]x-(1-2x)+(x-3)=-4\\x-1+2x+x-3=-4\\4x-4=-4\\4x=-4+4\\4x=0\,|\div4\\\boxed{x=0}[/tex]
e) [tex]5y-3[7-(1-2y)]=0\\5y-3[7-1+2y]=0\\5y-21+3-6y=0\\-y-18=0\\-y=18\,|\cdot(-1)\\\boxed{y=-18}[/tex]
b) [tex](5-y)+(6-y)-(5-y)=0\\5-y+6-y-5+y=0\\-y+6=0\\-y=-6\,|\cdot(-1)\\\boxed{y=6}[/tex]
d) [tex](x+3)-2x-(1-3x)=2\\x+3-2x-1+3x=2\\2x+2=2\\2x=2-2\\2x=0\,|\div2\\\boxed{x=0}[/tex]
f) [tex]15[4(x+2)-(3-x)]=4\\15[4x+8-3+x]=4\\15[5x+5]=4\\75x+75=4\\75x=4-75\\75x=-71\,|\div75\\\boxed{x=-\frac{71}{75}}[/tex]
Odpowiedź:
a) (x - 13) - (x - 5) + 2x = 0
x - 13 - x + 5 + 2x = 0
2x = 8
x = 4
b) (5 - y) + (6 - y) - (5 - y) = 0
5 - y + 6 - y - 5 + y = 0
y - 6 = 0
y = 6
c) x - (1 - 2x) + (x - 3) = - 4
x - 1 + 2x + x -3 = (-4)
4x - 4 = (-4)
4x = 0
x = 0
d) (x+3)-2x-(1-3x)=2
x + 3 - 2x - 1 + 3x =2
2x + 2 = 2
2x = 0
x = 0
e) 5y - 3[7 - (1 - 2y)] = 0
5y - 21 + 3 (1 - 2y) = 0
5y - 21 + 3 - 6y = 0
- y -18 = 0
y = - 18
f) 1 5 *[4(x+2)-(3-x)]=4
60(x + 2) - 15(3 - x) = 4
60x + 120 - 45 + 15x = 4
75x + 75 = 4
75x = - 71
x = -71/75